Evidence of a role for cAMP in mitochondrial regulation in ovarian granulosa cells. (9th August 2022) - Kaseder, Melanie; Schmid, Nina; Eubler, Katja; Goetz, Katharina; Müller-Taubenberger, Annette; Dissen, Gregory A; Harner, Max; Wanner, Gerhard; Imhof, Axel; Forne, Ignasi; Mayerhofer, Artur
Abstract: In the ovary, proliferation and differentiation of granulosa cells (GCs) drive follicular growth. Our immunohistochemical study in a non-human primate, the Rhesus monkey, showed that the mitochondrial activity marker protein cytochrome c oxidase subunit 4 (COX4) increases in GCs in parallel to follicle size, and furthermore, its intracellular localization changes. This suggested that there is mitochondrial biogenesis and trafficking, and implicates the actions of gonadotropins, which regulate follicular growth and ovulation. Human KGN cells, i.e. granulosa tumour cells, were therefore used to study these possibilities. To robustly elevate cAMP, and thereby mimic the actions of gonadotropins, we used forskolin (FSK). FSK increased the cell size and the amount of mitochondrial DNA of KGN cells within 24 h. As revealed by MitoTracker™ experiments and ultrastructural 3D reconstruction, FSK treatment induced the formation of elaborate mitochondrial networks. H89, a protein kinase A (PKA) inhibitor, reduced the network formation. A proteomic analysis indicated that FSK elevated the levels of regulators of the cytoskeleton, among others (data available via ProteomeXchange with identifier PXD032160). The steroidogenic enzyme CYP11A1 (Cytochrome P450 Family 11 Subfamily A Member 1), located in mitochondria, was more than 3-fold increased by FSK, implying that the cAMP/PKA-associated structural changes occur in parallel with the acquisition of steroidogenic competence of mitochondria in KGN cells. In summary, the observations show increases in mitochondria and suggest intracellular trafficking of mitochondria in GCs during follicular growth, and indicate that they may partially be under the control of gonadotropins and cAMP. In line with this, increased cAMP in KGN cells profoundly affected mitochondrial dynamics in a PKA-dependent manner and implicated cytoskeletal changes.